PERMAINAN HALANG RINTANG TERHADAP KEMAMPUAN GERAK DASAR LOKOMOTOR ANAK AUTIS - NISWAH, MAGHFIROTUN (Jurnal Pendidikan Khusus, 2016)
ABSTRACT Autism children had motoric hindrance in the form of the appearance of stereotype behavior (such as clapping and moving body), impulsivity, and hyperactive or adversely hypoactive. In addition there was motoric coordination retarded, tiptoe walking, clumsiness, could play with the peers, lack of attitude exactness and body movement, twisting, very hyperactive, jumping and flapping hands, etc. so the basic movement of locomotor was limited compared with the peers. The basic movement of locomotor was the movement which was done by human in general such as walking, running, jumping, leaping, etc. Every human always did this movement in every activity. To develop the basic movement of locomotor ability the autism children needed games modified exactly to enhance the basic movement of locomotor ability. This research had used obstacle-block game as the exact game to enhance the basic movement of locomotor ability for autism children. This research used quantitative approach with pre experiment kind, and used “One group pretest – posttest design”, with 6 autism students in SDN 7 Sidokumpul Gresik as the subject, each of them had initial: MI, MR, HH, AN, IA, and RD. This research used the design through a test before giving treatment (O1) once and after giving treatment (O2) twice, so there was comparison between O1 and O2 to know the treatment effectiveness X, the treatment was given 8 times. The data obtained was analyzed by statistic non parametric with sign test. From the result of statistic test in the research of the influence of obstacle-block game toward the basic movement of locomotor ability to autism children in SDN 7 Sidokumpul Gresik, it indicated that Zh value obtained was 2,05 greater than crisis value 5% i.e. 1,96 so Ho (null hypothesis) was refused and Ha (work hypothesis) was accepted. The work hypothesis above was proven that “The obstacle-block game influenced toward the basic movement of locomotor ability to autism children in SDN 7 Sidokumpul Gresik”.   Keywords: Basic movement of locomotor, obstacle-block game